Longterm Evaluation of Hemoglobin A1c Following Hepatitis C Therapy in Patients with and without HIV Co-infection. (4th October 2017) - Chaudhury, Chloe; Sheehan, Julia; Chairez, Cheryl; Akoth, Elizabeth; Gross, Chloe; Kattakuzhy, Sarah; Rosenthal, Elana; Kottilil, Shyam; Masur, Henry; Hadigan, Colleen
Abstract: Background: Historically, eradication of HCV with interferon-based treatments was linked with decreased incidence of diabetes. While viral clearance with direct acting agents (DAAs) may be associated with acute decreases in fasting glucose levels and hemoglobin A1c (HbA1c), there remains a need for larger prospective studies to address the longterm impact of sustained viral response (SVR) achieved with DAAs on glucose metabolism. Methods: Prospective longitudinal cohort study of 251 subjects with chronic HCV (100% genotype 1a/b, 31% HIV+, 17% diabetes) evaluated pre- and post-DAA therapy with median follow-up of 28 mos. Change in HbA1c, glucose, lipid and transaminase levels were compared based on SVR, HIV, diabetes status and fibrosis stage. Results: There was no difference in change in HbA1c between subjects who achieved SVR ( n = 241) compared with those who did not. Mean change in HbA1c did not differ from zero (−0.022 ± 0.53%) for those with SVR. Further, when subjects were grouped based on HIV, diabetes or fibrosis stage, there were no significant differences in changes in HbA1c or glucose following SVR. Subjects with HIV had smaller reductions in transaminase values (change ALT −33.3 ± 51 IU/L HIV+ vs. −47.8 ± 45 IU/L HIV-, P = 0.0007). Following SVR, total and LDL cholesterol increased ( P = 0.0002 and P = 0.0003, respectively) whereas triglyceride levels decreased ( P = 0.008). A greater proportion of subjects (7%) started or increased medication therapy for diabetes following SVR compared with the percentage who decreased diabetes therapy (3%). There was a statistically significant positive correlation between change in BMI and change in HbA1c (r=0.17, P = 0.006). Conclusion: The current study failed to identify sustained benefits in glucose or HbA1c in HCV treated patients, irrespective of HIV, diabetes or fibrosis stage. HIV infection blunted improvements in transaminase levels related to SVR. While HbA1c did not improve with HCV clearance, alterations in lipids were identified that warrant further investigation. Disclosures: C. Gross, Merck: stock holder, Own stock; Pfizer: stock holder, Own stock; JohnsonandJohnson: stock holder, Own stock